PRKCSH Alternative Splicing Involves in Silica-Induced Expression of Epithelial-Mesenchymal Transition Markers and Cell Proliferation - Ruixue Huang; Xiaodan Liu; He Li; Huacheng Ning; Ping-Kun Zhou (SAGE Publishing, 2020)
Background: Mounting evidence suggests that alternative splicing is one of the ways for cells to adapt to environmental stress insults. The aim of this study was firstly to examine the effect of silica on the alternative splicing of lung fibrosis-associated genes. Methods: Microarray analysis was used to construct the alternative splicing profile. Functional experiments were conducted using Cell Counting Kit-8, cell cycle, apoptosis, and epithelial-mesenchymal transition (EMT) analyses. Alternative splicing variants were verified by quantitative real-time polymerase chain reaction (qRT-PCR) polymerase chain reaction method. Results: A total of 1850 genes that have alternative splices in response to silica insult were identified. PCDHB11, MALAT1, MT2A, RP11-126D17.1, and RP11-415I12.2 are the top 5 upregulated genes with occurrence of alternative splice, whereas NDE1, RNPEPL1, TREML2, CSF2RB, and PRKCSH are the top 5 downregulated genes with occurrence of alternative splice. Bioinformatic analysis showed these genes with the occurrence of alternative splice mainly are associated with EMT pathway, N-Glycan biosynthesis, and leukocyte transendothelial migration. Further study indicated that PRKCSH-2 knockdown promotes A549 cell proliferation potential by partially promoting EMT signals. Conclusions: Significant changes in alternative splicing of silicosis-associated genes occur in patients with silicosis in silica conditions. Our study provides basic founding for further investigation into the detail molecular mechanisms underlying silica-induced silicosis.